PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2020 (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
This study aims to analyze how the effect of profitability and liquidity on stock prices in pharmaceutical sub-sector companies listed on the IDX 2017-2020. The sampling method was targeted sampling for 4 years from 9 selected companies, and the number of samples was 36. This study used a quantitative approach using secondary data sources downloaded from IDX's official website. Processing data using the SPSS application and carrying out several stages of analysis, namely descriptive statistics, normality test, multicollinearity test, autocorrelation test, heteroscedasity test, determination coefficient test, hypothesis test, and T test. The results show that profitability and liquidity from 2017 to 2020 did not significantly affect the stock prices of IDX-listed pharmaceutical companies.